The Role of Parental Mediation in the Relationship between Adolescents’ Use of Social Media and Family Relationships in Saudi Arabia - Najwa Albeladi; Emma Palmer (Journal of Information Technology Management)
This study aimed to examine the impact of parenting mediation strategies on family relationships and social media use among Saudi adolescents. To achieve the aim, a quantitative research design was used, involving questionnaires with data collected from 393 Saudi students aged 13-18 years. Pearson correlation and hierarchical multiple regression analyses were performed. The key findings of this study showed that Snapchat and Instagram were the most popular social media sites among Saudi adolescents, and parenting mediation strategies were affected by family relationships. Just over a third of participants (35.62%) reported that they spent 3-5 hours per day on social media with another 30.79% spending more than 6 hours per day on social media. Family relationships were found to strongly predict the social integration and social media addiction. The data showed a significant negative correlation between excessive use of social media and two components of family relationships (cohesion and expressiveness). Moreover, the results suggest that lower levels of family expressiveness and higher levels of family conflict were associated with social media addiction. The parenting mediation strategies were shown to predict the cohesiveness and expressiveness of family relationships. Finally, technical and monitoring parenting mediation strategies were found significant associated with the social media use and the family relationships. These results contribute to formulating guidelines for parents and policymakers in developing countries such as Saudi Arabia to protect their children from the social media risks.